Swahili phrasebook & dictionary - Berglund, Elin (Lonely Planet, 2014)
Lonely Planet's Swahili Phrasebook & Dictionary is your handy passport to culturally enriching travels with the most relevant and useful Swahili phrases and vocabulary for all your travel needs. With language tools in your back pocket, you can truly get to the heart of wherever you go, so begin your journey now!